Depression and paternal adjustment and attitudes during the transition to parenthood - Pinto, Tiago Miguel (2020)
Background: Depression symptoms may negatively affect the achievement of developmental tasks within the transition to parenthood, increasing the risk of paternal adjustment problems and negative paternal attitudes. Objective: This study analysed the effect of men's depression symptoms on paternal adjustment and paternal attitudes trajectories from the second trimester of pregnancy to six months postpartum. Methods: A sample of 127 men completed measures of depression symptoms and paternal adjustment and paternal attitudes at the second trimester of pregnancy and at six months postpartum. Results: From the second trimester of pregnancy to six months postpartum, men with more depression symptoms revealed a decrease on positive attitudes towards sex (while men with fewer depression symptoms revealed an increase), a steeper decrease in the satisfaction with marital relationship (than men with fewer depression symptoms), and a decrease in positive attitudes towards pregnancy and the baby (while men with fewer depression symptoms revealed an increase). Conclusion: Depression symptoms early in pregnancy may represent a risk factor to increased paternal adjustment problems and negative paternal attitudes during the transition to parenthood.